Yilan Kardeşler - Gilman, Charles; Smith, Eugene (Illustrator) (Istanbul : ABM Yayinevi., 2013)
Twins Sarah and Sylvia Price, two monsters in disguise at Lovecraft Middle School, are campaigning for student council with a secret plan to abduct the entire seventh grade, and Robert Arthur and his strange friends must stop their evil plot.
Keywords: Middle schools -- Juvenile fiction; Paranormal fiction; Schools -- Juvenile fiction; Teachers -- Juvenile fiction; Middle schools -- Fiction; Schools -- Fiction; Supernatural -- Fiction; Teachers -- Fiction; Paranormal fiction